Apostles Before Paul and During Paul’s Times - Kacian, Adrian (Communications - Scientific letters of the University of Zilina, 2007)
The concept of apostle before Paul and during his times was broad enough to embrace three groups of people - the Jerusalem appearance apostles, wandering Hellenistic missionaries commissioned by the Holy Spirit and representatives of congregation. Influenced by the Jewish legal institution of “messenger”, Jesus sent out his disciples for a temporary and nationally limited pre-resurrection mission. Twenty years or so after the resurrection, the existence of two missionary concepts of apostle (the Jerusalem appearance apostles, wandering missionaries) reflects the two communities in the primitive Church (Palestinian Jewish Christianity, Hellenistic Jewish Christianity) that implemented Jesus’ pre-resurrection concept. Paul, starting as a wandering missionary apostle, grounded his apostolate in the Christ event and thus marked the trajectory of apostle concept development that ultimately ended as a restrictive category for the Twelve only.